SPL Conqueror: Toward optimization of non-functional properties in software product lines - Siegmund, Norbert; Rosenmüller, Marko; Kuhlemann, Martin; Kästner, Christian; Apel, Sven; Saake, Gunter (Software quality journal, 2012)
A software product line (SPL) is a family of related programs of a domain. The programs of an SPL are distinguished in terms of features, which are end-user visible characteristics of programs. Based on a selection of features, stakeholders can derive tailor-made programs that satisfy functional requirements. Besides functional requirements, different application scenarios raise the need for optimizing non-functional properties of a variant. The diversity of application scenarios leads to heterogeneous optimization goals with respect to non-functional properties (e.g., performance vs. footprint vs. energy optimized variants). Hence, an SPL has to satisfy different and sometimes contradicting requirements regarding non-functional properties. Usually, the actually required non-functional properties are not known before product derivation and can vary for each application scenario and customer. Allowing stakeholders to derive optimized variants requires us to measure non-functional properties after the SPL is developed. Unfortunately, the high variability provided by SPLs complicates measurement and optimization of non-functional properties due to a large variant space. With SPL Conqueror, we provide a holistic approach to optimize non-functional properties in SPL engineering. We show how non-functional properties can be qualitatively specified and quantitatively measured in the context of SPLs. Furthermore, we discuss the variant-derivation process in SPL Conqueror that reduces the effort of computing an optimal variant. We demonstrate the applicability of our approach by means of nine case studies of a broad range of application domains (e.g., database management and operating systems). Moreover, we show that SPL Conqueror is implementation and language independent by using SPLs that are implemented with different mechanisms, such as conditional compilation and feature-oriented programming.